Friday

February 27, 2015

February 27, 2015

Posted by **Latianna** on Thursday, February 9, 2012 at 5:36pm.

- Math -
**Steve**, Thursday, February 9, 2012 at 9:12pmy=f(x), so x=f^-1(y)

y = 4x+12

y-12 = 4x

y/4 - 3 = x

f^-1(y) = y/4 - 3

so, f^-1(x) = x/4 - 3

**Answer this Question**

**Related Questions**

math - The cost of producing q articles is given by the function C=f(q)=100+2q...

algebra - 1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). ...

Math 3 - Find the inverse of the function f(x) = 5 – e^(x-1). Determine the ...

pre calculus - Find the inverse of the function below. Graph the function below ...

College Algebra - Find the inverse of the function below. Graph the function ...

precalculus - Find the inverse of the function below. Graph the function below ...

Maths B - (a) What is the inverse of the function y = 3x2 ? (b) On the same set ...

Pre-Calculus - Find the inverse function for the function f(x)=2^(x)+1/2^(x)-1 ...

math - Could you show me step by step how to find the inverse of this problem: ...

Algebra - Myra uses an inverse variation function to model the data for the ...